(untitled) (Minerva, 2017)
This paper focuses on a miscellany compiled by the Jesuit author Andreas Schott. Within its interesting contents, the miscellany collects unkown post-incunabula and manuscripts of the Spanish humanist Antonio de Nebrija. One of the works of Nebrija is De anni correctione, unknown until recently and now edited and translated.